Teaching Method In Writing Descriptive Text (A Descriptive Study at the Seventh Grade Students of Thammislam Foundation School Academic Year 2023) - Fahri Akbar, Pirman Ginting (Pusdikra Publishing, 2023)
This study investigates the instructional approach English teachers employ in teaching descriptive writing to seventh-grade students at Thammislam Foundation School during the Academic Year 2023. What challenges does the English teacher encounter when instructing seventh-grade students at Thammislam Foundation School during the Academic Year 2023 in the area of writing descriptive texts? The research objectives are categorized into three distinct areas: writing, descriptive text, and the instructional methods employed by English teachers. The present study employed a descriptive qualitative research design. The researcher assumed the role of a non-participant observer. The researcher conducted three observations in a seventh-grade classroom and interviewed with an English teacher to gather information about the instructional methods employed in teaching descriptive writing. The observed population comprises 28 students enrolled in the seventh grade at Thammislam Foundation School during the academic year of 2023. The data collection instruments employed in this study encompassed observation, interviews, and the examination of relevant study documents, including modules, student worksheets, and curriculum materials. The researcher employed a three-step process to analyze the data. The three main components of the research process include data reduction, data display, and conclusion verification. Researchers employ triangulation as a means to enhance the trustworthiness of the data. The research findings indicate that the activities conducted by the teacher during the initial and subsequent meetings were consistent with the principles and framework of task-based language teaching. Implementing task-based language teaching in a classroom typically involves three distinct stages: the pre-task stage, the task cycle, and the language focus stage. The challenges encountered by the student included a limited vocabulary and a need for more proficiency in selecting appropriate verbs for constructing sentences. The instructor assigned exercises to enhance the students' vocabulary and proficiency in selecting the appropriate verb for each sentence. The models used for the tasks were evaluated based on their ability to match the given criteria accurately. In addition, the instructor employed a systematic approach to facilitate comprehension among the students, particularly in the context of composing descriptive texts.